Ichthyofauna of Merbau River, Leuser Ecosystem Area, Indonesia: species composition, diversity, biometric condition, potency, and conservation status - M. Hidayat; S. Maulizar; A. S. Batubara; N. Kautsari; H. Latuconsina; F. M. Nur; I. Zulfahmi (The European Zoological Journal, 2023)
AbstractThe Leuser Ecosystem Area (LEA) is one of the largest conservation areas in Southeast Asia. However, the explorations of ichthyofauna at LEA are still relatively scarce compared to other vertebrates fauna. We report the first ichthyofauna studies of the northern river of LEA in Aceh Province. This study aimed to determine the composition, diversity, biometric condition, potency, and conservation status of freshwater fish in Merbau River, LEA, Indonesia. Fish sampling was carried out at six research stations using selective gill nets, throwing net, hook, tray net, and scoop net. A total of 434 individual fish belonging to 21 species, nine families and six orders were collected from the sampling location. Cyprinidae was the predominant family obtained, namely 42.9%. Based on their conservation status, 85.7% of collected fish were categorized as Least Concern, 9.5% as Data Deficient, and 4.8% as Near Threatened. A total of 14 fish have the potential as consumption fish, two species have the potential as ornamental fish, and five others have the potential both as consumption and ornamental fish. All fish species collected had negative allometric growth patterns with growth coefficient values (b) ranging from 1.17–2.51. The diversity and evenness index of fish was categorized as moderate (H’ = 2.52) with stable conditions (E = 0.85).